Mindfulness and its Relationship to Psychological Resilience and Academic Achievement of High School Students - Alshahrani, Munira Awthah; Alwalidi, Ali Mohammad (Journal of Educational and Psychological Sciences, 2022)
The objective of the research is to define the relationship between Mindfulness, psychological resilience and academic achievement of High School Student. The objective of the research is to define the relationship between Mindfulness, psychological resilience and academic achievement of High School Student. To achieve this goal, the descriptive correlation method was used, and the research sample consisted of (350) high school students in The Governorate of One Raveida who were randomly selected. To achieve this goal, the descriptive correlation method was used, and the research sample consisted of (350) high school students in The Governorate of One Raveida who were randomly selected. The two study tools were applied to them electronically because of the conditions imposed by The VCE and Corona B, both of the five factors of mental awakening, (Baer,et al., 2006), translated by (Al-Buhairi, et al., 2014) and the psychological resilience measure )Connor & Davidson, 2003), translated by H.E. Hashimia (2017). The two study tools were applied to them electronically because of the conditions imposed by The VCE and Corona B, both of the five factors of mental awakening, translated by others (2014) and the psychological resilience measure translated by H.E. Hashimia (2017). The research reached several conclusions, there is a positive, statistically significant correlation between each dimension of mental alertness, mental alertness in general and psychological resilience among secondary school students. It was also found that there is a positive, statistically significant correlation between each of the following dimensions of mental alertness (description, conscious behavior, not judging internal experiences) mental alertness in general, and academic achievement among secondary school students, it was also found that there was no statistically significant correlation between each of the following dimensions of mental alertness (observation, lack of interaction with internal experiences) and academic achievement among secondary school students. And it was found that there is a positive, statistically significant correlation between psychological resilience and academic achievement among secondary school students. The results also showed that the psychological resilience and academic achievement of secondary school students can be predicted through mental alertness, and the academic achievement of secondary school students can be predicted through psychological resilience. The study recommends the need to integrate mental alertness activities into the curricula of secondary school students, and to encourage students to practice these activities, which helps them develop positive habits that contribute to supporting their mental and physical health in the future. The study also recommends the need to improve psychological flexibility of a secondary school student through Practical activities and exercises that contribute to making them more able to face academic challenges, overcome them and positively adapt to them, by developing their skills by dealing with failed experiences with positive self-compassion and acceptance and full openness to their experiences and tolerance towards them, which makes them compatible and reconciled with themselves and others.